1970
DOI: 10.1029/rs005i003p00611
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Characteristics of Longitudinal Waves From an Antenna in a Plasma

Abstract: This paper describes experiments designed to measure the radiation patterns of a longitudinal wave excited in a warm plasma by both monopole and dipole antennas. The longitudinal wave used in this experiment is the low‐frequency ion acoustic wave that propagates with a phase velocity [γkTe/M/i]½. Experimental results agree well with the theoretical predicted radiation pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1972
1972
1986
1986

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A cylindrical dipole [Balmain, 1965;Lin and Mei, 1968;Wunsch, 1968;Schiff, 1971], a slotted sphere [Wait and Spies, 1966], and a loop antenna [Morita and E•lashira, 1974;Ohnuki et al, 1977], which are classified as balanced-fed antennas, have been studied hitherto. On the other hand, the unbalanced-fed antennas such as a spherical antenna [Fejer, 1964;Balmain, 1966;Tarstrup and Heikkila, 1972;Aso, 1973], and a disc antenna [Shen et al, 1970;Ohnuma et al, 1974;Ohnuki and Adachi, 1981;Ohnuki et al, 1978], which are commonly cited papers involving plasma waves, have also been investigated. In the analyses of the unbalanced-fed antennas, in general, the current on a transmission line feeding the antenna has been neglected so far to avoid the mathematical complexity of the problem.…”
Section: Introductionmentioning
confidence: 99%
“…A cylindrical dipole [Balmain, 1965;Lin and Mei, 1968;Wunsch, 1968;Schiff, 1971], a slotted sphere [Wait and Spies, 1966], and a loop antenna [Morita and E•lashira, 1974;Ohnuki et al, 1977], which are classified as balanced-fed antennas, have been studied hitherto. On the other hand, the unbalanced-fed antennas such as a spherical antenna [Fejer, 1964;Balmain, 1966;Tarstrup and Heikkila, 1972;Aso, 1973], and a disc antenna [Shen et al, 1970;Ohnuma et al, 1974;Ohnuki and Adachi, 1981;Ohnuki et al, 1978], which are commonly cited papers involving plasma waves, have also been investigated. In the analyses of the unbalanced-fed antennas, in general, the current on a transmission line feeding the antenna has been neglected so far to avoid the mathematical complexity of the problem.…”
Section: Introductionmentioning
confidence: 99%
“…Grids, disks, and wires are used to excite and to detect electrostatic waves such as the electron plasma wave, the ion acoustic wave, and so on. Radiation patterns'from these antennas have been measured and compared with theoretical ones using the far field approximation and the neglect of any wave damping [Shen et al, 1970;Nakamura et al, 1973]. Extensive reviews of this topic have recently been written [Ohnuma, 1978;Balmain, 1979].…”
Section: Introductionmentioning
confidence: 99%
“…We first review some of the relevant results which pertain to the present experiment. Shen et al [ 1970] demonstrated that it is possible to predict and measure the radiation pattern of ion-acoustic waves from a solid circular disc in a plasma. Burde [ 1975] derived a reciprocity relation for these ion-acoustic waves which was later generalized by Ishizone et al [1976].…”
Section: Introductionmentioning
confidence: 99%